Reason, value, and respect Kantian themes from the philosophy of Thomas E. Hill, Jr - Timmons, Mark 1951-; Johnson, Robert N. (Oxford University Press, 2015)
In 13 specially written essays, leading philosophers explore Kantian themes in moral and political philosophy that are prominent in the work of Thomas E. Hill, Jr., such as respect and self-respect, practical reason, conscience, and duty. In conclusion Hill offers an overview of his work and responses to the preceding essays
Keywords: Hill, Thomas E.; Kant, Immanuel / 1724-1804 / Influence; Hill, Thomas E. -- 1937-; Philosophy, American / 20th century; Kantianismus; Aufsatzsammlung